2013
DOI: 10.1002/iid3.9
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of IL‐1α, IL‐1β and TNF to the host response to Mycobacterium tuberculosis and attenuated M. bovis BCG

Abstract: TNF and IL-1 are major mediators involved in severe inflammatory diseases against which therapeutic neutralizing antibodies are developed. However, both TNF and IL-1 receptor pathways are essential for the control of Mycobacterium tuberculosis infection, and it is critical to assess the respective role of IL-1α, IL-1β, and TNF. Using gene-targeted mice we show that absence of both IL-1α and IL-1β recapitulates the uncontrolled M. tuberculosis infection with increased bacterial burden, exacerbated lung inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 62 publications
7
65
0
Order By: Relevance
“…Cellular structures known as necrotic granulomas may promote bacterial dissemination and enhance Mtb transmission [2,3]. On the other hand, counter balance is supported by host recognition of Mtb, which induces cytokines such as IL-1β and TNF [4,5], two potent inflammatory mediators that suppress Mtb growth [4,6]. It has C 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.eji-journal.eu Eur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular structures known as necrotic granulomas may promote bacterial dissemination and enhance Mtb transmission [2,3]. On the other hand, counter balance is supported by host recognition of Mtb, which induces cytokines such as IL-1β and TNF [4,5], two potent inflammatory mediators that suppress Mtb growth [4,6]. It has C 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.eji-journal.eu Eur.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular structures known as necrotic granulomas may promote bacterial dissemination and enhance Mtb transmission [2,3]. On the other hand, counter balance is supported by host recognition of Mtb, which induces cytokines such as IL-1β and TNF [4,5], two potent inflammatory mediators that suppress Mtb growth [4,6]. It has been shown that these cytokines regulate intracellular bacterial growth in human macrophages, whether by recruitment of antimicrobial effector molecules [7] or induction of apoptotic cell death [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IRAK-4 is an adaptor molecule downstream of IL-1R signaling. Bourigault et al (41) showed that IL-1 signaling is important for controlling M. tuberculosis infection but is dispensable for the host immune response to M. bovis BCG, although IL-1b is produced in response to both pathogens. However, treatment of IRAK 2/2 macrophages with IFN-g and IL-1b did not improve M. tuberculosis intracellular killing at 72 h postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…2). Measurement of alveolar wall thickening in lungs is an important parameter to determine lung inflammation (41).…”
Section: Lack Of Irak-4 Compromises Liver Granuloma Formationmentioning
confidence: 99%
“…Rapid Mtb growth and the death of the host have been clearly demonstrated following TNF-a blockade in vitro, in vivo, and in knockout mouse models, revealing the protective role of this cytokine in Mtb infection (Bruns et al, 2009;Jozefowski et al, 2011;Bourigault et al, 2013;Roh et al, 2013). Conversely, IL-10 has been found at increased levels in tuberculosis patients, and elevated innate production of IL-10 is associated with greater susceptibility to this disease (Cooper et al, 2011;Sakamoto, 2012).…”
Section: Discussionmentioning
confidence: 99%